The waiting process: a grounded theory study of families' experiences of waiting for patients during surgery - Sadeghi, Tabandeh; Nayeri, Nahid Dehghan; Abbaszadeh, Abbas (Journal of research in nursing, 2015)
In this qualitative study, conducted with a grounded theory approach, 17 family members awaiting their relatives’ surgery, were interviewed. The interviews were semi-structured and the data from them was analysed using the constant comparative method suggested by Corbin and Strauss. The findings showed ‘attempt to reassure’ as the core category. The main theme of ‘assurance’, comprising patterns of ‘recourse to spirituality’, ‘communication’, ‘physical proximity’, and ‘coping’ indicated the processes used by participants to achieve their goals. These findings may help health care professionals, especially nurses, to better understand the subject and better facilitate the process of waiting whilst relatives have surgery.